2012
DOI: 10.1037/a0027946
|View full text |Cite
|
Sign up to set email alerts
|

Age, gender, and arousal in recognition of negative and neutral pictures 1 year later.

Abstract: Compared with nonarousing stimuli, arousing stimuli enhance memory performance. The most robust effects have been reported for negative stimuli, "the negativity effect," although a number of mediating factors prevent definitive conclusions, for example, age, gender, memory task, retention period, and alternative arousal measures. To clarify whether the negativity effect is robust across age, gender, and time, we studied incidental recognition of neutral and negative pictures from the International Affective Pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 88 publications
4
17
0
Order By: Relevance
“…However, a recent study from our lab with a retention interval of 1 year demonstrated better memory accuracy for negative compared to neutral scenes in both younger and older adults (Gavazzeni et al, 2012). This further highlights the importance of retention intervals and might reflect that very long-term consolidation of negative scenes may result in a re-established negativity effect in both age groups.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…However, a recent study from our lab with a retention interval of 1 year demonstrated better memory accuracy for negative compared to neutral scenes in both younger and older adults (Gavazzeni et al, 2012). This further highlights the importance of retention intervals and might reflect that very long-term consolidation of negative scenes may result in a re-established negativity effect in both age groups.…”
Section: Discussionmentioning
confidence: 77%
“…For the older group, however, it is difficult to state that increased right AMG activity for successfully recognized negative scenes compared with neutral scenes subtended a delayed negativity effect: Considering the discrimination findings, although performance seemed to stabilize compared to S2 in the old, and normalize compared to the younger group, the fact that performance was low prevents firm conclusions. However, a beneficial effect of AMG activity on performance can be hypothesized when considering hits only, where the negativity effect appeared at S3 in the older group (see also Gavazzeni et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such effects have also been shown in certain picture memory tasks (Charles, Mather, & Carstensen, 2003). There have also been some discrepant findings (e.g., Grühn, Smith, & Baltes, 2005) and some controversy about whether positivity effects should be regarded only as Age × Valence interactions (Reed & Carstensen, 2012) or whether there may be important reasons to also consider offset in processing between positive/negative and neutral (Gavazzeni, Andersson, Bäckman, Wiens, & Fischer, 2012;Murphy & Isaacowitz, 2008). Nonetheless, this general framework has exerted a quite significant impact on the study of socioemotional aging and on emotion-cognition links in the context of age.…”
Section: The View From Socioemotional Selectivity Theorymentioning
confidence: 85%
“…Fifth, in future studies it would appear important to control in the analyses for potential differences in time spent on the self‐paced recognition task. Sixth, the role of physiological responses at stimulus encoding and recognition for memory performance would be another issue to investigate (Gavazzeni, Anderson, Bäckman, Wiens & Fischer, ; Hämmerer et al ., ). Finally, interpretation of the results regarding age‐related vs. cohort effects requires caution because of the cross‐sectional study design.…”
Section: Discussionmentioning
confidence: 99%